2008
DOI: 10.1007/s10562-008-9476-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Divalent Metal Component (MeII) on the Catalytic Performance of MeIIFe2O4 Catalysts in the Oxidative Dehydrogenation of n-Butene to 1,3-Butadiene

Abstract: A series of metal ferrite (Me II Fe 2 O 4 ) catalysts were prepared by a co-precipitation method with a variation of divalent metal component (Me II = Zn, Mg, Mn, Ni, Co, and Cu) for use in the oxidative dehydrogenation of n-butene to 1,3-butadiene. Successful formation of metal ferrite catalysts with a random spinel structure was confirmed by XRD, ICP-AES, and XPS analyses. The catalytic performance of metal ferrite catalysts in the oxidative dehydrogenation of n-butene strongly depended on the identity of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Figure 5 shows the correlation between yield for 1,3-butadiene and surface weak-acid density of ZnMe IIIFeO 4 catalysts. The correlation clearly shows that yield for 1,3-butadiene was closely related to the surface weak-acid density of ZnMe III FeO 4 catalysts, in good agreement with the previous works [12,[23][24][25][26]. Yield for 1,3-butadiene increased with increasing surface weak-acid density of the catalyst.…”
Section: Correlation Between Catalytic Performance and Acid Propertysupporting
confidence: 91%
See 2 more Smart Citations
“…Figure 5 shows the correlation between yield for 1,3-butadiene and surface weak-acid density of ZnMe IIIFeO 4 catalysts. The correlation clearly shows that yield for 1,3-butadiene was closely related to the surface weak-acid density of ZnMe III FeO 4 catalysts, in good agreement with the previous works [12,[23][24][25][26]. Yield for 1,3-butadiene increased with increasing surface weak-acid density of the catalyst.…”
Section: Correlation Between Catalytic Performance and Acid Propertysupporting
confidence: 91%
“…Therefore, it is expected that surface acid-base properties of ferrite-type catalyst play a very important role in the oxidative dehydrogenation of n-butene. It has been reported in our previous works [12,23,24] that the catalytic performance of zinc ferrite catalyst in the oxidative dehydrogenation of n-butene was closely related to the surface acid density of the catalyst.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This means that surface acid-base property of ZnFe 2 O 4 catalyst plays a very important role in the oxidative dehydrogenation of n-butene. It has been reported in our previous works [11,19,21,25,26] that the catalytic performance of ZnFe 2 O 4 catalyst in the oxidative dehydrogenation of n-butene was closely related to the surface acid density of the catalyst.…”
Section: Introductionmentioning
confidence: 78%
“…Recently, Song et al [9][10][11] have focused on the preparation of two types of catalysts such as ferrite catalysts and multicomponent bismuth molybdate catalysts [12][13][14][15][16][17][18][19][20][21][22][23][24] and found that catalytic performance could be improved by pH control [9,15,20], divalent metal substitution [11], or calcination condition [24].…”
Section: Introductionmentioning
confidence: 99%